Induction of labour: Facilitation of labour onset, prediction of success and improving the induction process / Tan Peng Chiong - Tan, Peng Chiong (2014)

(untitled)
Labour is induced in about 25% of pregnancies demonstrating its importance in contemporary obstetric practice. The papers forming the thesis are grouped as follows surrounding the central theme of inducing labour: 1) Coitus as a home remedy and membrane sweeping as an office procedure to facilitate onset of labour The works on coitus provide important lessons about human studies. The initial promise from an observational study demonstrating an association of coitus with earlier labour onset was not supported by the findings of two subsequent clinical trials on coitus as an intervention. The secondary data analysis of the first trial also provide evidence that coitus at term does not facilitate labour onset. The paper on serial weekly membrane sweeping to facilitate labour onset in women desiring vaginal birth after Caesarean did not demonstrate statistically significant results but the observed effect is smaller than assumed. 2) Evaluation of sonographic predictors of successful induction of labour resulting in vaginal delivery The works on ultrasound parameters as predictors of successful labour induction contributed to the developing literature. We confirmed that transvaginal ultrasound is better tolerated than digital assessment for the Bishop Score. This can be important for iii maternal satisfaction in obstetric care. Transvaginal ultrasound measurement of cervical length is probably a better predictor of labour inducibility than Bishop Score but additional equipment and skill acquisition are needed. Our original study linking membrane sweeping and cervical length changes as assessed by transvaginal ultrasound demonstrate a positive association between postsweep cervical shortening and subsequent vaginal delivery. Postsweep cervical shortening may be a marker of cervical pliability leading to labour success. 3) Novel refinements of currently used labour induction regimens to improve efficiency in high, mixed and low risk populations. The work on membrane sweeping as an immediate adjunct to formal labour induction is important as it confirms that adjunctive membrane sweeping reduces operative delivery. Concurrent titrated oxytocin infusion and dinoprostone pessary in nulliparas with intact membranes and unfavourable cervixes is a viable option based on our largely positive findings. The few past trials on concurrent regimens all used quite different regimens; any meta-analysis would be difficult to constitute and interpret. On the other hand in nulliparas with unfavourable cervixes after term prelabour rupture of membranes, labour induction with titrated oxytocin infusion is possibly better leaving little rationale for a future concurrent regimen trial. The case for immediate titrated oxytocin infusion following amniotomy for labour induction in parous women with favourable cervixes is more balanced. Immediate oxytocin is quicker at achieving vaginal delivery but minor abnormality in fetal heart rate tracing is also more common.